Neuroprotective effect of rice and corn extracts against H2O2-induced neurotoxicity in HT22 murine hippocampal neuronal cells - Chumpiya S; Plaingarm W; Tewin Tencomnao (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Oxidative stress-induced neuronal damage, mediated by the cellular accumulation of hydrogen peroxide (H2O2), was reported to be involved in neurodegenerative diseases. Rice and corn may serve as sources of antioxidants with the presence of phytochemicals such as melatonin and tryptophan, for fighting against reactive oxygen species (ROS). Melatonin are known to upregulate the expression of brain-derived neurotrophic factor (BDNF) gene for enhancement of the nerve cell function and mediation of the anti-aging effect of the brain cells. The present study aimed at determining the effect of white rice, brown rice, black glutinous rice, sweet corn and baby corn extracts against H2O2-induced neurotoxicity and their underlying mechanisms in the mouse hippocampal HT22 cells. Following pretreatment of the HT22 cells with individual extract for 24 hrs and subsequent challenge with H2O2 for 24 hrs, cell viability, apoptosis, intracellular ROS and BDNF gene expression were measured. Rice and corn extracts were evaluated for their antioxidant activities and the levels of tryptophan and melatonin. Characteristics of H2O2-induced neurotoxicity included decreased cell viability, increased cellular ROS and decreased BDNF expression. Pretreatment with rice and corn extracts significantly attenuated H2O2-induced neurotoxicity, and also significantly decreased ROS production. Pretreatment with these extracts could also upregulate the expression of BDNF mRNA and protein, which may be contributed by their melatonin and tryptophan contents. Therefore, rice and corn extracts may protect HT22 cells against H2O2-induced neurotoxicity by inhibition of ROS production and modulation of BDNF expression.